THE MARKET DYNAMICS OF THE TOURISM DEMAND IN BOTOȘANI COUNTY DURING THE PERIOD 2009-2018 - Cristina SIMEANU; Radu-Adrian MORARU; Benone PĂSĂRIN; Daniel SIMEANU; Dan BODESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The present study highlights aspects regarding the evolution of the table grape market in Romania, between 20142018. Table grapes are appreciated on the one hand, because of the pleasant taste, and on the other hand for the therapeutic value offered by them. At the national level the areas cultivated with vines specialized in table varieties are much smaller, compared to the areas cultivated with vines specialized in varieties for wine. In this study, a series of indicators were analyzed, such as: the total area occupied by vineyards in bearing; the surface of vineyards specialized in table varieties; total table grapes production; average prices for table grapes; consumption of table grapes; valoric imports and exports. The statistical data analyzed in the present study were provided mainly by the National Institute of Statistics.